2022
DOI: 10.1155/2022/4841241
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment and Design of a Distributed Hybrid Energy System for Rural Electrification: The Case for Jamataka Village, Botswana

Abstract: This research focuses on an assessment and design of a hybrid Photo Voltaic (PV)-wind system for rural electrification in Jamataka village, Botswana. The assessment revealed the most pressing factors for the need for reliable energy and the issues that the village community had with existing electricity sources. Hybrid Optimization of Multiple Energy Resources (HOMER) software was used to perform all the hybrid system configurations, simulations, and selections. The assessment research was carried out using qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Liberia is one of the world's Least Developed Nations (LDNs), with about 64% of the population living below the poverty line and about 1.3 million living in extreme poverty (RREA, 2018;Fortune Business Insights, 2020-2027MCC, 2018;Mohantya et al, 2018;Gildas Fosso et.al.,2023;Clint Ameri et.al.,2023;Mahdavi et al, 2023;Mulenga et al, 2023). Additionally, 3.7 million Liberians lack access to clean water; 80% are foodinsecure; the child labor rate is 21%, compounded by many slum communities (Milbrant Anelia, 2009;Ministry of Lands and Mines and Energy MLME, 2009;Pachauri and Shonali, 2017b;Nations Encyclopedia, 2021;Samikannu et al, 2022;Ahmed et al, 2023;Mishra et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Liberia is one of the world's Least Developed Nations (LDNs), with about 64% of the population living below the poverty line and about 1.3 million living in extreme poverty (RREA, 2018;Fortune Business Insights, 2020-2027MCC, 2018;Mohantya et al, 2018;Gildas Fosso et.al.,2023;Clint Ameri et.al.,2023;Mahdavi et al, 2023;Mulenga et al, 2023). Additionally, 3.7 million Liberians lack access to clean water; 80% are foodinsecure; the child labor rate is 21%, compounded by many slum communities (Milbrant Anelia, 2009;Ministry of Lands and Mines and Energy MLME, 2009;Pachauri and Shonali, 2017b;Nations Encyclopedia, 2021;Samikannu et al, 2022;Ahmed et al, 2023;Mishra et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Utilizing renewable energy sources in the mix of electricity generation through hybrid systems significantly reduces carbon emissions, and in particular, a combination of photovoltaic/wind/hydroelectric hybrid systems is the most efficient combination in combating climate change (WMO, 2021). A case study of the Jamataka village, Botswana electrification project under SolaNetwork has shown that PV/wind/ battery hybrid combination is a viable option in terms of Net Present Cost and emissions (Samikannu et al, 2022). An analysis of the feasibility and financial implications of implementing a hybrid energy system combining photovoltaic and biomass in rural areas of Bangladesh indicates that this kind of system is cheaper and more sustainable than conventional kerosene-based systems (Our World in Data, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been found, despite differences in methodology, that hybrid designs often lead to optimal and cost-effective solutions [19][20][21][22][23][24]. As part of the effort to provide electricity to rural areas in remote locations, a techno-economic feasibility study was conducted [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The lowest net present cost (NPC) was obtained with PV-wind-diesel-biomass [22], PV-wind-battery [23], and PV-battery [24]. In [22], PV was identified as the most suitable primary energy source.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The government established an isolated solar microgrid system of 5.7 kW capacity with battery storage in the village of Motshegaletau to power a school, clinic, some residential houses, and a business centre (Situmbeko, 2018). A hybrid PV-wind system was evaluated and designed to provide electricity for the rural areas of Jamataka village in Botswana's north-eastern region (Ravi et al, 2022). The survey was conducted to determine the power consumption of the households in the village.…”
Section: Introductionmentioning
confidence: 99%